Ghrelin Attenuates Neuroinflammation and Demyelination in Experimental Autoimmune Encephalomyelitis Involving NLRP3 Inflammasome Signaling Pathway and Pyroptosis - Liu, Fei; Li, Zijian; He, Xin; Yu, Haiyang; Feng, Juan (Frontiers in Pharmacology, 2019)
Multiple sclerosis (MS) is a chronic autoimmune and degenerative disease of the central nervous system, and conventional treatments have limited efficacy or side effects. Ghrelin, a 28-amino acid octanoylated peptide, has been reported to have neuroprotective effects, including anti-oxidation, inflammation, and anti-apoptosis. Pyroptosis, also called inflammatory cell death, is triggered by overly active inflammasomes and accompanied by the production of numerous cytokines. As immune dysfunction is primarily involved in the pathogenesis of MS, this study aimed to explore the therapeutic effects and precise functional mechanisms of ghrelin against the NLRP3 inflammasome and pyroptosis in experimental autoimmune encephalomyelitis (EAE). Sprague Dawley rats were immunized with guinea pig spinal cord homogenates and pertussis toxin to develop an EAE model. All rats were randomly divided into 4 groups: normal control group, EAE group, EAE + ghrelin group, and ghrelin control group. EAE rats showed abnormal behavioral scores and body weight changes. Histologic analysis displayed severe inflammatory infiltration and demyelination in the brain and spinal cord of EAE rats. Ghrelin treatments potently restored these abnormal changes. In addition, the ghrelin-treated EAE group showed significantly down-regulated expression of inflammatory cytokines. The expression of proteins involved in the NLRP3 signaling pathway and pyroptosis was decreased as well. We also found that the anti-inflammatory effect of ghrelin was associated with inhibition of NF-κB activation. Compared with rats in the healthy control group, rats in the ghrelin control group did not show statistically significant changes in histologic examinations, pro-inflammatory cytokine productions or molecules involved in the NLRP3 signaling pathway, which indicated that ghrelin induced no side effects in the animals of our study. Our findings provide more insight into the use of ghrelin as a novel candidate for MS.